Influence of habitat heterogeneity on anuran diversity in Restinga landscapes of the Parnaíba River delta, northeastern Brazil - Kássio C. Araújo; Anderson Guzzi; Robson Avila (ZooKeys, 2018)
Anurans have close associations with environmental conditions and therefore represent an interesting vertebrate group for examining how resource availability and environmental variables influence species diversity. Associations between habitat heterogeneity and anuran species diversity were tested in the Restinga landscapes of the Parnaíba River delta in northeastern Brazil. Twenty-one anuran species were sampled in the rainy season during monthly excursions (December 2015 to June 2016) into areas of Restinga on two islands in the Parnaíba River delta. The fourth highest anuran diversity was found in this type of environment in Brazil and is the third in northeastern Brazil. Microenvironments, characterized by a combination of vernal pools with different vegetational and physical structures, better explained anuran species composition in the Parnaíba River delta.